PEMANFAATAN KINEMASTER DALAM PEMBUATAN VIDEO PEMBELAJARAN IPA SD UNTUK GURU DAN MAHASISWA - Muqarrobin, Tamman Firdaus; Sumarno, Sumarno (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2021)
"This study aims to understand the usefulness of the kinemaster application in terms of making science learning videos in elementary schools. This study uses a descriptive quantitative research design. The data collection technique used is a questionnaire. The results showed that: 1) 65% of respondents admitted that they did not understand how to make a good learning video. 2) Almost all respondents, around 86% stated that they were very familiar with the kinemaster application, but did not really know how to use it. 3) 60% of respondents said they did not understand how to use the kinemaster application to make learning videos. 4) Of the several obstacles in making learning videos, 80% of the respondents stated that it was very difficult to develop learning materials that would be included in the learning videos. 5) 85% of respondents stated that by using the kinemaster application, making learning videos became easier">